2016
DOI: 10.1155/2016/1069743
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myeloperoxidase in Patients with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a worldwide public health problem. Patients with CKD have a number of disorders in the organism, and the presence of oxidative stress and systemic inflammation in these patients is the subject of numerous studies. Chronic inflammation joined with oxidative stress contributes to the development of numerous complications: accelerated atherosclerosis process and cardiovascular disease, emergence of Type 2 diabetes mellitus, development of malnutrition, anaemia, hyperparathyroidism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 90 publications
1
53
0
2
Order By: Relevance
“…This is in contrast with the report of Capeillere-Blandin et al who showed a significantly higher level of myeloperoxidase in ESKD patients on hemodialysis when compared to non-dialysis CKD patients [40]. Increase in myeloperoxidase after hemodialysis [41], its differential regulation by hemodialysis membrane type [42,43], duration of dialysis, and variation in background variables such as anthropometric measures [44], comorbidities and medication use suggest their confounding rules in myeloperoxidase level [45]. The change in 3-ClY is less frequently studied in CKD.…”
Section: Discussionmentioning
confidence: 89%
“…This is in contrast with the report of Capeillere-Blandin et al who showed a significantly higher level of myeloperoxidase in ESKD patients on hemodialysis when compared to non-dialysis CKD patients [40]. Increase in myeloperoxidase after hemodialysis [41], its differential regulation by hemodialysis membrane type [42,43], duration of dialysis, and variation in background variables such as anthropometric measures [44], comorbidities and medication use suggest their confounding rules in myeloperoxidase level [45]. The change in 3-ClY is less frequently studied in CKD.…”
Section: Discussionmentioning
confidence: 89%
“…Macrophages are closely associated with atherogenesis and represent a major source of oxidative stress in CKD (51,67). However, the role of macrophage derived MPO in CKD associated atherosclerosis is yet to be explored using mechanistic models, as non-CKD animal models of atherosclerosis that demonstrate clear MPO involvement are not established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MPO-derived protein carbamylation is associated with CVD in the CKD population (46)(47)(48)(49). Plasma MPO levels increase with each stage of CKD and are linked to CVD mortality in patients with end-stage renal disease (ESRD) who are undergoing peritoneal dialysis (50)(51)(52)(53). In a recent study, our group reported that both MPO and 3-chlorotyrosine levels rise in the presence of CAD at various stages of CKD (54).…”
mentioning
confidence: 99%
“…35 Third, CKD induces systemic inflammation, a condition considered to increase the risk of AAA. 27, 36 Finally, neovascularization has been reported to play an important role in the pathophysiology of AAA, 37 and given that CKD is a clinical phenotype of microvascular disease, it is possible that those with CKD are more likely to have abnormal aortic neovascularization compared to those without CKD. 38 Nonetheless, future studies are needed to explore these and other pathophysiological mechanisms, which may link CKD, particularly albuminuria, to AAA.…”
Section: Discussionmentioning
confidence: 99%